A prebiotic galactooligosaccharide mixture reduces severity of hyperpnoea-induced bronchoconstriction and markers of airway inflammation - Williams, Neil C.; Johnson, Michael A.; Shaw, Dominick E.; Spendlove, Ian; Vulevic, Jelena; Sharpe, Graham R.; Hunter, Kirsty A. (Cambridge University Press, 2016)
Gut microbes have a substantial influence on systemic immune function and allergic sensitisation. Manipulation of the gut microbiome through prebiotics may provide a potential strategy to influence the immunopathology of asthma. This study investigated the effects of prebiotic Bimuno-galactooligosaccharide (B-GOS) supplementation on hyperpnoea-induced bronchoconstriction (HIB), a surrogate for exercise-induced bronchoconstriction, and airway inflammation. A total of ten adults with asthma and HIB and eight controls without asthma were randomised to receive 5·5 g/d of either B-GOS or placebo for 3 weeks separated by a 2-week washout period. The peak fall in forced expiratory volume in 1 s (FEV1) following eucapnic voluntary hyperpnoea (EVH) defined HIB severity. Markers of airway inflammation were measured at baseline and after EVH. Pulmonary function remained unchanged in the control group. In the HIB group, the peak post-EVH fall in FEV1 at day 0 (−880 (sd 480) ml) was unchanged after placebo, but was attenuated by 40 % (−940 (sd 460) v. −570 (sd 310) ml, P=0·004) after B-GOS. In the HIB group, B-GOS reduced baseline chemokine CC ligand 17 (399 (sd 140) v. 323 (sd 144) pg/ml, P=0·005) and TNF-α (2·68 (sd 0·98) v. 2·18 (sd 0·59) pg/ml, P=0·040) and abolished the EVH-induced 29 % increase in TNF-α. Baseline C-reactive protein was reduced following B-GOS in HIB (2·46 (sd 1·14) v. 1·44 (sd 0·41) mg/l, P=0·015) and control (2·16 (sd 1·02) v. 1·47 (sd 0·33) mg/l, P=0·050) groups. Chemokine CC ligand 11 and fraction of exhaled nitric oxide remained unchanged. B-GOS supplementation attenuated airway hyper-responsiveness with concomitant reductions in markers of airway inflammation associated with HIB.